Education Development Strategy for Children with Disabilities: On the Way to Implementing a Cultural-Historical Approach - Karabanova O.A.,; Malofeev N.N., (Культурно-историческая психология, 2020)
The relevance of developing a strategy for the development of education for children with disabilities and limited health is due to the need to create a developmental educational environment that meets the educational needs of this category of children in the context of modernization of general education and the implementation of inclusive/integrated education. The purpose of the article is to analyze the key provisions of the strategy, its scientific novelty and practical significance for the modernization of the education of children with disabilities. From the point of view of the cultural-historical approach (L.S. Vygotsky, A.R. Luria, D.B. Elkonin), the priority of early assistance to children at risk is substantiated in order to create conditions for ensuring the normative age development of children with developmental risk factors. The desired educational outcomes are presented as specific age-related psychological neoformations/higher mental functions for early, preschool, primary, secondary and high school age. The paper highlights the necessity of creating a new psychological and pedagogical typology that implements the principle of variety of developmental options for the same impairment while maintaining the nosological criterion. For early, preschool and primary school age, a psychological and pedagogical typology is proposed based on the characteristics of child development, risk factors, developmental disabilities and their genesis. Based on theoretical and empirical studies and psychological practices, it is proved that the target group of early assistance in education is a family raising a child with disabilities, with special educational needs. Monitoring the developmental interaction between the family and the child with disability is an important component of the psychological support as this interaction is essential to the correction and prevention of developmental disorders. Differentiating between the academic achievements and life competencies as the planned educational outcomes of programmes for children with disabilities would create the foundation for positive socialisation and social integration of the disabled children.